2020
DOI: 10.1155/2020/8835544
|View full text |Cite|
|
Sign up to set email alerts
|

Augmented Reality Interface for Complex Anatomy Learning in the Central Nervous System: A Systematic Review

Abstract: The medical system is facing the transformations with augmentation in the use of medical information systems, electronic records, smart, wearable devices, and handheld. The central nervous system function is to control the activities of the mind and the human body. Modern speedy development in medical and computational growth in the field of the central nervous system enables practitioners and researchers to extract and visualize insight from these systems. The function of augmented reality is to incorporate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 94 publications
0
8
0
3
Order By: Relevance
“…Durch die Nutzung von mHealth entstehen extrem große Datensätze, die beispielsweise aus elektronischen Gesundheitsakten, medizinischen Bildern und anderen komplizierten Texten bestehen, welche nur schlecht interpretiert werden können bzw. bei welchen die Analyse durch den Menschen sehr viel Zeit in Anspruch nimmt [ 18 ]. Daher wird die Entwicklung der mobilen Gesundheitsangebote als Treiber für den Aufbau intelligenter Gesundheitssysteme betrachtet.…”
Section: Artificial Intelligence In Der Medizinunclassified
See 2 more Smart Citations
“…Durch die Nutzung von mHealth entstehen extrem große Datensätze, die beispielsweise aus elektronischen Gesundheitsakten, medizinischen Bildern und anderen komplizierten Texten bestehen, welche nur schlecht interpretiert werden können bzw. bei welchen die Analyse durch den Menschen sehr viel Zeit in Anspruch nimmt [ 18 ]. Daher wird die Entwicklung der mobilen Gesundheitsangebote als Treiber für den Aufbau intelligenter Gesundheitssysteme betrachtet.…”
Section: Artificial Intelligence In Der Medizinunclassified
“…Damit würde ein digitaler Experte entstehen, welcher beispielsweise Pathologieergebnisse automatisiert in einen Bericht umwandelt [ 15 ]. Die künstliche Intelligenz besitzt weiterhin die Fähigkeit, automatisch zu lernen, sich zu verbessern, ohne explizit dafür programmiert zu werden, also maschinell zu lernen [ 18 ]. Durch die Nutzung von Algorithmen kann ein solches Computersystem in kurzer Zeit weitaus mehr Informationen und auch Erfahrungen abrufen, als es für einen Menschen möglich ist [ 19 ].…”
Section: Artificial Intelligence In Der Medizinunclassified
See 1 more Smart Citation
“…A literature review conducted from an engineering approach was centered on considering AR applications developed with contents of the nervous system and based on gesture interaction (Wirza et al, 2020). The review showed that the use of AR technology for the visualization of the nervous system increased over the last three years.…”
Section: Introductionmentioning
confidence: 99%
“…IoT promotes various application areas, such as smart health, [4][5][6][7][8][9][10][11][12][13] smart city, [14,15], environment monitoring [16,17] smart home, [18,19], traffic management [20][21][22][23][24], smart education system, [25], smart farming, [26,27], and many others [28][29][30][31][32][33][34][35]. In smart cities, various problems occur when devices communicate with each other; one of the important problems is waste management.…”
Section: Introductionmentioning
confidence: 99%